A note on weakly Lindelöf frames. Issue 6 (18th August 2018) - Abedi, Mostafa
Abstract: The notion of σ ∗ -properness of a subset of a frame is introduced. Using this notion, we give necessary and suﬃcient conditions for a frame to be weakly Lindelöf. We show that a frame is weakly Lindelöf if and only if its semiregularization is weakly Lindelöf. For a completely regular frame L, we introduce a condition equivalent to weak realcompactness based on maximal ideals of the cozero part of L . This enables us to show that every weakly realcompact almost P -frame is realcompact. A new characterization of weakly Lindelöf frames in terms of neighbourhood strongly divisible ideals of ᎡᏞ is provided. The closed ideals of ᎡᏞ equipped with the uniform topology are applied to describe weakly Lindelöf frames.